Efficacy and Safety of NaoShuanTong Capsule in the Treatment of Ischemic Stroke: A Meta-Analysis - Zhang, Hanlai; Xing, Yanwei; Chang, Jingling; Wang, Liqin; An, Na; Tian, Chao; Yuan, Mengchen; Yang, Xinyu; Shang, Hongcai; Gao, Ying; Gao, Yonghong (Frontiers in Pharmacology, 2019)
Background: Ischemic stroke (IS) is a leading cause of death and long-term disability worldwide. NaoShuanTong capsule (NSTC), a traditional Chinese patent medicine, has been extensively used in the treatment of stroke in China. However, the clinical efficacy and safety of this treatment has not been statistically and systematically verified by any comprehensive pooled analysis. We therefore performed a meta-analysis to evaluate the efficacy and safety of NSTC in the treatment of IS. Methods: Randomized controlled trials (RCTs) of NSTC in the treatment of IS conducted before September 2018 were retrieved from five databases, according to specific inclusion and exclusion criteria. Two investigators independently reviewed the included studies and extracted relevant data. The methodological quality of the included studies was assessed using criteria from the Cochrane Handbook, and analyzed using Review Manager 5.3 software. Results: Thirteen RCTs comprising a total of 1,360 participants were included in this study. NSTC was shown to significantly improve the overall response rate (OR = 3.04, 95% CI [1.76, 5.26], P < 0.00001), and neurological function (NSTC increased Modified Barthel Index (MD = 8.15, 95% CI [3.79, 12.52], P = 0.0005), Functional Independence Measure (MD = 29.61, 95% CI [10.11, 49.10], P = 0.003) and European Stroke Scale scores (MD = 8.51, 95% CI [7.00, 10.01], P = 0.03). In addition, NSTC significantly increased serum adiponectin level (MD = 0.66, 95% CI [0.23, 1.08], P = 0.002). Moreover, NSTC reduced atherosclerotic plaque area (MD = -2.24, 95% CI [-4.02, -0.46], P = 0.01) and intima-media thickness (MD = -0.09, 95% CI [-0.13, -0.05], P < 0.0001). However, there was no significant difference between NSTC treatment and conventional therapy with respect to Fugl-Meyer Assessment score (MD = 10.59, 95% CI [-1.78, 22.96], P = 0.09) or Crouse score (MD = -0.78, 95% CI [-1.79, -0.22], P = 0.13). Conclusions: The results of this meta-analysis showed that NSTC exhibits efficacy in the treatment of cerebral infarction. NSTC can improve the overall response rate and neurological function, increase blood adiponectin, reduce neurological deficits, and decrease atherosclerotic plaque area.